2020
DOI: 10.1029/2020jd032666
|View full text |Cite
|
Sign up to set email alerts
|

n‐Alkanes and PAHs in the Southeastern Tibetan Plateau: Characteristics and Correlations With Brown Carbon Light Absorption

Abstract: The samples of atmospheric total suspended particle (TSP) were obtained at the remote Tibetan site (named Lulang) from November 2015 to November 2016. The seasonal characteristics of n-alkanes, polycyclic aromatic hydrocarbons (PAHs) variations, and their correlations to brown carbon (BrC) light absorption in TSP were investigated. Elevated TSP n-alkanes and PAHs levels were observed in winter (2.8 and 10 times higher than in monsoon, respectively), largely due to the seasonal contributions of wintertime home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…These observations suggest that PAC is an important fraction determining the light absorption properties of MS-BrC. Recent studies found strong correlations between PAHs and light absorptivity of MS-BrC in remote and urban regions (Tibetan Plateau and urban Xi’an, China). , The priority PAHs are useful tracers of MPAC, as found in the present study. Further studies are required to determine whether there are strong relations between MPAC and the light absorptivity of MS-BrC for ambient aerosols.…”
Section: Resultssupporting
confidence: 85%
“…These observations suggest that PAC is an important fraction determining the light absorption properties of MS-BrC. Recent studies found strong correlations between PAHs and light absorptivity of MS-BrC in remote and urban regions (Tibetan Plateau and urban Xi’an, China). , The priority PAHs are useful tracers of MPAC, as found in the present study. Further studies are required to determine whether there are strong relations between MPAC and the light absorptivity of MS-BrC for ambient aerosols.…”
Section: Resultssupporting
confidence: 85%
“…So, the factor characterized by medium to high MW PAHs were linked with coal combustion. This factor had the second highest average contribution to Abs 365,m (18.5%, Table S6 in the Supporting Information S1), supporting that PAHs could act as one category of water-insoluble BrC chromophores (Huang et al, 2020;Zhu et al, 2020). These three fossil fuel-related primary sources were also identified in urban Denver, USA Xie, Piedrahita et al, 2013;Xie et al, 2014), and had more contributions to Abs 365,m than Abs 365,w (Table S6 in the Supporting Information S1).…”
Section: Pmf Source Apportionmentmentioning
confidence: 82%
“…focused on BC and BrC measured using a seven wavelengths Aethalometer (Zhu et al, 2017(Zhu et al, , 2021, or the correlations between special components (e.g., PAHs) and BrC in the southeastern HTP site (Zhu et al, 2018;Zhu, Li, et al, 2020;Zhu, Zhang et al, 2020). There are high uncertainties in the estimation of BrC radiative forcing and source apportionments due to inadequate observations and constrains in modeling, impeding accurate estimation of its warming effects in the HTP.…”
Section: Introductionmentioning
confidence: 99%